Rethinking flourishing: Critical insights and qualitative perspectives from the U.S. Midwest - Sarah S. Willen; Abigail Fisher Williamson; Colleen C. Walsh; Mikayla Hyman; William Tootle, Jr (Elsevier, 2022)
In recent years, human flourishing and its relationship to mental health have attracted significant attention in a wide range of fields. As an interdisciplinary, mixed-methods team with strong roots in critical medical anthropology and critical public health, we are intrigued by the possibility that a focus on flourishing may reinvigorate health research, policy, and clinical care in transformative ways. Yet current proposals to this effect, we contend, must be met with caution. In particular, we call attention to the troubling disconnect between current research on flourishing, on one hand, and the voluminous body of scholarship demonstrating the detrimental impact of structural inequities on health, on the other. We illuminate this blind spot in two ways. We begin with a critical assessment of leading conceptions of flourishing in positive psychology, which are compared to current approaches in the critical social sciences of health. In the second half of the paper, we support our argument by presenting original findings from a mixed-methods study with a diverse sample of interviewees in the Midwestern U.S. city of Cleveland, Ohio (n=167). Our interviewees' rich narrative accounts, which we analyze both quantitatively and qualitatively, highlight important ways in which everyday understandings of flourishing diverge from prevailing scholarly accounts. Given these gaps and blind spots, now is an opportune time for robust interdisciplinary discussion about the implicit values and presumptions underpinning leading approaches to flourishing and their wide-ranging implications for research, policy, and clinical care in mental health fields and beyond.